Seedling growth and photosynthetic characteristics of different Sophora moorcroftiana provenances - ZHAO Yuwen; DUAN Shaorong; ZHENG Yu; NAN Jibin; Misang; ZHAO Yalei; LIN Ling (浙江大学学报. 农业与生命科学版, 2019)
In order to study the difference on seedling growth and photosynthetic characteristics among Sophora moorcroftiana provenances, the growth characters, chlorophyll content, and curves of light response and CO2 response were analyzed, using eight provenances of one-year-old seedlings. The results showed that there was a significant difference on the growth and chlorophyll content among the provenances of S. moorcroftiana seedlings (P<0.05). The light response curve showed that the net photosynthetic rate (Pn) increased as the increasing photosynthetically active radiation (PAR). When the Pn of eight provenances increased to the top, it decreased irrespective of increasing PAR and represented the single-peak curve, with an obvious photo inhibition phenomenon. The light saturation point (LSP) of eight provenances ranged from 740.467 to 1 773.078 μmol/(m2·s), and light compensation point (LCP) ranged from 1.408 to 43.381 μmol/(m2·s). The Pn and LSP of provenances in Linzhou County and Bayi District were higher than these of other provenances. The CO2 response curve showed that the concentration of CO2 increased within a certain range. The characteristic parameters of CO2 curve showed statistical differences among the provenances (P<0.05). The CO2 saturation point (CSP) was between 1 769.632 and 2 678.136 μmol/(m2·s) and the CO2 compensation point (Г) was between 76.155 and 111.430 μmol/ (m2·s). Correlation analysis showed that the Pn was positively correlated with stomatal conductance (Gs) and LSP (P<0.01), and the intercellular CO2 concentration (Ci) was significantly correlated with transpiration rate (Tr), LCP and dark respiration rate (Rd) (P<0.01). Seedling height was significantly correlated with Pn and the content of chlorophyll (P<0.05). The provenances of Linzhou County and Bayi District had higher Pn, and their LSP were also the highest, which indicated that these two provenances had high photosynthetic potential under the strong light environment.